Social Context, Self-Efficacy, and Patient-Centered Service Behavior of Medical Professionals: The Moderating Role of Achievement Motivation - Huang, Xianhong; Wang, Cong; Hua, Le; Gao, Yuan; Zhou, Siyu; Wang, Xiaohe (Frontiers in Psychiatry, 2022)
Patient-centered services are high-value, high-quality medical services that can improve patient satisfaction and safety. However, little is known about their driving mechanisms. This study examined whether external (social context) and internal (self-efficacy) motivation affects medical professionals' patient-centered service behavior, and explored the moderating role of medical professionals' achievement motivation. A cross-sectional survey was conducted with medical professionals at public hospitals in Hangzhou. Descriptive statistics, hierarchical linear regression analysis, and structural equation modeling were used to analyze the data. The final analysis included 1,612 medical professionals. Results indicated that perceived social context and self-efficacy had direct and positive effects (β = 0.578, β = 0.269) on medical professionals' patient-centered service behavior. Social context also indirectly influenced medical professionals' patient-centered service behavior mediated by self-efficacy (β = 0.149). Additionally, achievement motivation played a moderating role (β = −0.037) between the social context and self-efficacy. From the results it can be deduced that an excellent social environment and strong self-efficacy can promote the patient-centered service motivation of medical professionals. This promoting effect is even more significant under the moderating effect of high achievement motivation. Governments, health administrative departments, and hospital management should use internal and external motivation factors to promote medical professionals' patient-centered service behavior. Along with formulating relevant laws and regulations, efforts should also be made to guide medical professionals to improve their self-efficacy and achievement motivation, thereby encouraging patient-centered medical service behavior.